Evaluation of a Multithreaded Architecture for Cellular Computing - Caşcaval, Călin; Castaños, José G.; Ceze, Luís; Denneau, Monty; Gupta, Manish; Lieber, Derek; Moreira, José E.; Strauss, Karin; Warren, Jr Henry S. (HPCA 2002 (High Performance Computer Architecture), 2002)
Cyclops is a new architecture for high performance parallel computers being developed at the IBM T. J. Watson Research Center. The basic cell of this architecture is a single-chip SMP system with multiple threads of execution, embedded memory, and integrated communications hardware. Massive intra-chip parallelism is used to tolerate memory and functional unit latencies. Large systems with thousands of chips can be built by replicating this basic cell in a regular pattern. In this paper we describe the Cyclops architecture and evaluate two of its new hardware features: memory hierarchy with flexible cache organization and fast barrier hardware. Our experiments with the STREAM benchmark show that a particular design can achieve a sustainable memory bandwidth of 40 GB/s, equal to the peak hardware bandwidth and similar to the performance of a 128-processor SGI Origin 3800. For small vectors, we have observed in-cache bandwidth above 80 GB/s. We also show that the fast barrier hardware can improve the performance of the Splash-2 FFT kernel by up to 10%. Our results demonstrate that the Cyclops approach of integrating a large number of simple processing elements and multiple memory banks in the same chip is an effective alternative for designing high performance systems.